Kepemimpinan Lembaga Pendidikan Islam Pondok Pesantren Kyai Syarifuddin Lumajang - Syuhud; Muhammad Abdul Halim Sidiq (Idarotuna : Journal of Administrative Science, 2023)
The most fascinating aspect of management studies is the study of leadership. The field's context is dynamic and always changing, reflecting the ways in which human life is developed, including the role of leadership in Islamic educational institutions. Change always begins with a protracted process of altering society's fundamental ideals, which then affects people's communication styles, basic needs, and view on life. Organizational leadership is impacted by changes in this area of life while developing the organization's vision, mission, and strategies for achieving goals. As a result, this study is primarily concerned with how Islamic educational institutions will address society's everyday demands from a leadership standpoint in the future. Research on leadership cannot be limited to quantitative methods; qualitative methods will also yield deeper insights into the fundamental issues surrounding change. It is envisaged that qualitative studies will offer a summary of the data underlying certain concepts, ideas, and tactics used in educational institution management, which are crucial for altering course and accomplishing institutional objectives. The study's findings indicate that in order to achieve shared objectives, adjustments to organizational management must be made in addition to modifications to leadership typology. As a result, future developments in the leadership typology will affect the viability and caliber of Islamic education in Indonesia. In order to adapt to the challenges of change, Islamic educational institution leaders are today required to create organizational management that can mobilize all aspects and forces for organizational success.